2009
DOI: 10.1111/j.1600-0404.1995.tb00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Age at onset: the major determinant of outcome in Parkinson's disease

Abstract: Factors at presentation which influenced the course of the disease and response to treatment were assessed in 125 de novo patients with Parkinson's disease. Ninety‐eight patients were available for re‐assessment at 5 years. Older patients presented earlier after the onset of symptoms, deteriorated more rapidly, and were significantly more likely to develop dementia and impairment of balance. Increasing age and symmetrical disease predicted the new appearance of imbalance. Age of onset did not predict dyskinesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 44 publications
8
52
0
Order By: Relevance
“…Patients with advanced age at onset progress more rapidly to degrees of disability when compared to younger age groups. These results are in line with previous studies and confirm the findings from longitudinal studies that elderly age at onset of the disease may be associated with more rapid deterioration [13,14]. In fact, Birkmayer et al [15] identified a group of patients with PD submitting a ‘malignant progressive course', whose average age was 10 years older at onset than those patients with a more benign evolution.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Patients with advanced age at onset progress more rapidly to degrees of disability when compared to younger age groups. These results are in line with previous studies and confirm the findings from longitudinal studies that elderly age at onset of the disease may be associated with more rapid deterioration [13,14]. In fact, Birkmayer et al [15] identified a group of patients with PD submitting a ‘malignant progressive course', whose average age was 10 years older at onset than those patients with a more benign evolution.…”
Section: Discussionsupporting
confidence: 81%
“…By contrast, other authors did not find a link between the speed of progression and clinical forms [4,20]. Perhaps tremor represents a different underlying pathophysiologic process [13]. As seen in our cohort and as pointed in the study by Gasparoli et al [21], predictive models based on these clinical characteristics are effective in predicting a slow progression of the disease, However, most studies consistently link the predominant clinical AR form with a rapid progression of disability [16,21,22].…”
Section: Discussionmentioning
confidence: 82%
“…The literature regarding neuropsychological assessment of EOPD patients focuses on low rates of dementia in this population [2,24,32], with reports of cognitive deficits rare [24]. However, treatment of the motor aspects of PD is complex, and when cognitive and affective factors are taken into account, it becomes even more so.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive performance and MCI have been evaluated in less detail in EOPD despite the detrimental effects they could have on QoL and performance of everyday tasks in these patients, who develop the disease at an age when they have greater professional, family, and social commitments. The majority of studies investigating cognition in EOPD have focused on the fact that dementia rates are lower in EOPD than in LOPD [2,24,32], regardless of the evidence that cognitive dysfunction also occurs in patients without dementia [24]. …”
Section: Introductionmentioning
confidence: 99%
“…119,[120][121][122][123][124][125][126] Conflicting studies report that prominent tremor is associated with older age, 127 dementia 128 and to a lesser extent rapid disease progression. 128 Other data suggest few clinical differences between youngand old-onset PD, 129 although muscular stiffness and sensory symptoms may be a more common presentation in younger patients. 127 The variance in the literature may be partly explained by methodological differences and varying clinical populations, as well as bias in the use of retrospective study design.…”
Section: Sub-groups In Pdmentioning
confidence: 99%